Experimental Investigation and Characterization of Biodiesel From Aregmone ocheroleuca - Eyob Hailemichael Yimer; Eshetu Getahun; Dawit Tessema Ebissa (Energy Science & Engineering)
ABSTRACT The experimental investigation and characterization of biodiesel from Argemone ochroleuca involves extracting oil from plant seeds through processes such as solvent extraction or mechanical pressing. Following extraction, transesterification is performed to convert the oil into biodiesel, typically using an alcohol (like methanol) and a catalyst (such as sodium hydroxide or potassium hydroxide). The produced biodiesel can be characterized by analyzing properties such as viscosity, density, flash point, acid value, and cetane number, often employing techniques like gas chromatography and spectroscopy to evaluate composition and purity. Such studies are essential to determine the feasibility of utilizing Argemone ochroleuca as a sustainable biodiesel production feedstock and assess its performance compared to conventional fuels. This study discusses On the experimental investigation and characterization of biodiesel derived from Aregmone ochroleuca, a plant known for its oil‐rich seeds and also the production of biodiesel from argemone oil, methanol, and potassium hydroxide catalysis through transesterification methods. The experimental run on argemone seed oil, focusing on the effect of particle size on oil extraction yield and physicochemical properties of crude oil. The oil was pretreated with sulfuric acid to reduce its acid value. The physicochemical properties of biodiesel were compared with ASTM and EU standards, and it was found that a good correlation between experimental results and biodiesel standards was expected. The maximum seed oil yield of Argemone ochroleuca was obtained by Soxhlet extraction from a smaller particle size of ripe seeds, yielding 38.05%. The oil's yellowish color and slightly transparent liquid with a refreshing and pleasant odor indicate its freshness and flavor quality. Including acid value, free fatty acid, saponification value, specific gravity, density, kinetics viscosity, and ash content, the physicochemical properties of the oil were determined.